2013
DOI: 10.1186/gb-2013-14-5-r41
|View full text |Cite
|
Sign up to set email alerts
|

Genome of the long-living sacred lotus (Nelumbo nucifera Gaertn.)

Abstract: BackgroundSacred lotus is a basal eudicot with agricultural, medicinal, cultural and religious importance. It was domesticated in Asia about 7,000 years ago, and cultivated for its rhizomes and seeds as a food crop. It is particularly noted for its 1,300-year seed longevity and exceptional water repellency, known as the lotus effect. The latter property is due to the nanoscopic closely packed protuberances of its self-cleaning leaf surface, which have been adapted for the manufacture of a self-cleaning industr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
384
4
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 339 publications
(409 citation statements)
references
References 33 publications
(54 reference statements)
19
384
4
2
Order By: Relevance
“…At least one more polyploidy event was identified along the branches leading to all eudicot lineages depicted except Vitis [30,58,93,95]. Three independent polyploidy events were proposed on the terminal branch to Musa acuminata [34].…”
Section: Palaeopolyploidy and Gene Family Gainsmentioning
confidence: 98%
See 1 more Smart Citation
“…At least one more polyploidy event was identified along the branches leading to all eudicot lineages depicted except Vitis [30,58,93,95]. Three independent polyploidy events were proposed on the terminal branch to Musa acuminata [34].…”
Section: Palaeopolyploidy and Gene Family Gainsmentioning
confidence: 98%
“…This is somewhat in conflict with the other large gains, which usually accompanied one or more WGD events. The inconsistency could be due to the timing and nature of the gamma event, which may actually be two events that occurred in close proximity, very early in the evolutionary history of eudicots [93].…”
Section: Palaeopolyploidy and Gene Family Gainsmentioning
confidence: 99%
“…Like the SEP1-SQUA and SEP3-SFT tandems in Figure 4A, we found that the AGL6-TM3 tandem gene arrangement is widespread across angiosperms (Figures 4B and 4C; Supplemental Data Set 3). For example, there is one AGL6-TM3 tandem gene pair in A. trichopoda and two such tandems in N. nucifera likely due to the most recent WGD this species experienced (Ming et al, 2013;Wang et al, 2013) ( Figure 4C; Supplemental Data Set 3). In V. vinifera, we also found two AGL6-TM3 tandems ( Figure 4C; Supplemental Data Set 3) that likely originated from the g triplication after which one tandem lost its AGL6 locus.…”
Section: Ii2 Angiosperm-wide Conserved Agl6-tm3 Tandemmentioning
confidence: 99%
“…Notably, its seeds can survive for thousands of years, making it the oldest viable seed for which an age has been directly determined (Priestley and Posthumus, 1982). To date, the entire genomic sequence of N. nucifera has been published (Ming et al, 2013); however, the UBC gene has not yet been reported. Therefore, in this study, the UBC gene was cloned and characterized in N. nucifera.…”
Section: Introductionmentioning
confidence: 99%